Electrode catalyst layer for fuel cell and polymer electrolyte fuel cell equipped with said electrode catalyst layer
By coating titanium oxide carriers in fuel cells with niobium, tantalum, or silicon oxides, titanium elution is suppressed, maintaining catalyst activity and reducing resistance, thus improving fuel cell durability.
Patent Information
- Application Number
- JP2022503264
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-27
- Filing Date
- 2021-02-12
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-02-12
AI Technical Summary
Titanium oxide carriers in fuel cells elute during operation, leading to decreased catalyst activity and increased cell resistance, particularly under reducing conditions, affecting long-term durability.
Incorporating a coating oxide of niobium, tantalum, zirconium, or silicon on the surface of the titanium oxide carrier, with a controlled atomic ratio (A2/A1) to suppress titanium elution, maintaining catalyst activity and reducing cell resistance.
The solution effectively prevents titanium elution, maintaining high catalyst activity and reducing cell resistance, thereby enhancing the long-term durability of fuel cells.
Smart Images

Figure 0007610571000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode catalyst layer for a fuel cell, and also to a polymer electrolyte fuel cell provided with an electrode catalyst layer. [Background technology]
[0002] Titanium oxide is known as one of the supports used in the electrode catalyst layer of fuel cells. Titanium oxide is highly stable even when exposed to high potential, so it is considered a promising material to replace the carbon-based supports that have been used conventionally. For example, Patent Document 1 describes Ti n O 2n-1 The document describes the use of conductive particles, in which a conductive layer is formed by doping the surface of a parent phase of Magneli phase titanium oxide represented by the formula (n satisfying 4≦n≦10) with a Group 5 transition metal element such as niobium or tantalum, as a catalyst support. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-081584 A Summary of the Invention
[0004] In addition to the catalyst-supporting carrier, the electrode catalyst layer of a fuel cell contains a strongly acidic substance such as an ionomer. The solid electrolyte layer in contact with the electrode catalyst layer is also generally composed of a strongly acidic substance. Therefore, when the carrier made of titanium oxide comes into contact with such a strongly acidic substance during the operation of the fuel cell, titanium is likely to be eluted from the carrier. In particular, titanium is more likely to be eluted from the anode in a reducing atmosphere. The eluted titanium diffuses and re-precipitates, which is one of the factors that cause a decrease in catalytic activity and an increase in cell resistance. The elution of titanium is also one of the factors that cause a decrease in the long-term durability of the fuel cell.
[0005] Therefore, an object of the present invention is to suppress the elution of titanium during operation of a fuel cell that uses titanium oxide as a catalyst support while maintaining catalytic activity.
[0006] The present invention provides an electrode catalyst layer for a fuel cell, comprising a catalyst-supported carrier in which a catalyst is supported on a carrier, the support comprises titanium oxide; The catalyst-supporting carrier has an oxide of at least one element selected from the group consisting of niobium, tantalum, zirconium, and silicon on its surface, The above-mentioned problem has been solved by providing an electrode catalyst layer for a fuel cell, in which the value A2 / A1, which is the ratio of the atomic ratio A2 of the sum of niobium, tantalum, zirconium and silicon to the atomic ratio A1 of titanium on the surface of the catalyst layer as measured by X-ray photoelectron spectroscopy, is 0.35 or more and 1.70 or less. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention will be described below based on its preferred embodiments. The present invention relates to an electrode catalyst layer for a fuel cell, which includes a catalyst-supported carrier in which a catalyst is supported on a carrier. The carrier includes titanium oxide. The titanium oxide includes titanium element (Ti) and oxygen element (O), with the remainder preferably being composed of inevitable impurities. The carrier including titanium oxide is preferably conductive. An electrode catalyst layer including a catalyst-supported carrier is used in electrodes of various fuel cells. For example, it is used as an anode catalyst layer and / or a cathode catalyst layer of a polymer electrolyte fuel cell or a phosphoric acid fuel cell.
[0008] In the electrode catalyst layer of the present invention, the catalyst-supporting carrier contained in the catalyst layer contains an oxide of a specific element on its surface. Due to the presence of this oxide, in the present invention, the dissolution of titanium constituting the carrier can be effectively suppressed. From this viewpoint, it is advantageous to use, as the oxide, an oxide having an oxidation-reduction potential of 0V or close to it in a reducing atmosphere and in which the element is unlikely to dissolve in a low pH range (e.g., pH=0 to 1). Examples of such oxides include oxides of at least one element selected from niobium, tantalum, zirconium, and silicon. Hereinafter, oxides of these elements are conveniently referred to as "coating oxides".
[0009] The coating oxide is present on the surface of the catalyst-supporting carrier. In particular, the coating oxide can be present on the surface of the carrier at a portion where the catalyst is not supported. In addition, the coating oxide can be present on the surface of the catalyst. Alternatively, the coating oxide can be present on the entire surface of the catalyst-supporting carrier. The present inventors have found that the presence of the coating oxide in such a coated state can effectively suppress the elution of titanium constituting the carrier. In contrast to this, for example, the technology described in Patent Document 1 involves placing titanium oxide doped with niobium and / or tantalum on the surface of a support made of titanium oxide and supporting a catalyst thereon. However, with this type of design, it is not possible to suppress the elution of titanium from the support.
[0010] From the viewpoint of more effectively suppressing the elution of titanium from the carrier by disposing a coating oxide on the surface of the catalyst-supporting carrier, it is preferable to control the amount of coating oxide disposed on the surface of the catalyst-supporting carrier. The amount of coating oxide disposed on the surface of the catalyst-supported carrier can be easily measured, for example, by X-ray photoelectron spectroscopy (hereinafter also referred to as "XPS"). In the present invention, the atomic ratio A1 of titanium on the surface of the electrode catalyst layer measured by XPS and the atomic ratio A2 of the elements (excluding oxygen) constituting the coating oxide are measured, and the value of A2 / A1, which is the ratio of A2 to A1, is controlled. The elements constituting the coating oxide are one or more elements selected from niobium, tantalum, zirconium, and silicon. When two or more of these elements are contained in the coating oxide, A2 means the total ratio of all elements.
[0011] From the viewpoint of effectively suppressing the elution of titanium from the support, the ratio A2 / A1 is preferably 0.35 or more, and more preferably 0.45 or more, while from the viewpoint of preventing an increase in cell resistance due to an increase in coating oxide, A2 / A1 is preferably 1.70 or less, more preferably 1.50 or less, and particularly preferably 0.80 or less. The value of A2 / A1 can be controlled by appropriately setting the conditions for disposing the coating oxide on the catalyst-supporting carrier. The XPS measurement method for determining the values of A1 and A2 will be described in detail in the examples below. The value of A2 / A1 preferably satisfies the above-mentioned value when the electrode catalyst layer is in the state of itself, or preferably satisfies the above-mentioned value when the electrode catalyst layer is in the state of a catalyst-coated electrolyte membrane (hereinafter also referred to as "CCM") or a membrane electrode assembly (hereinafter also referred to as "MEA").Furthermore, it is preferable to incorporate the electrode catalyst layer into a fuel cell and satisfy the above-mentioned value before and / or after the operation of the fuel cell.
[0012] The coating oxide can be arranged on the surface of the catalyst-supported carrier in the form of particles. Alternatively, the coating oxide can be arranged on the surface of the catalyst-supported carrier in the form of a film. The form in which the coating oxide is arranged can be determined according to the type of element constituting the coating oxide. When the element constituting the coating oxide is, for example, one or more of niobium, tantalum, and zirconium, it is advantageous to arrange the coating oxide on the surface of the catalyst-supported carrier in the form of particles. This is because these elements are stable at a potential of 0V and a pH of 0 to 1 in the potential-pH diagram. On the other hand, when the element constituting the coating oxide is, for example, silicon, it is advantageous to arrange the coating oxide on the surface of the catalyst-supported carrier in the form of a film.
[0013] When the coating oxide is arranged on the surface of the catalyst-supported carrier in the form of particles, it is preferable that the particle diameter D1 of the coating oxide is smaller than the particle diameter D2 of the catalyst-supported carrier in order to more effectively suppress the elution of titanium from the carrier. In order to make this advantage more prominent, D1 is preferably 10% to 35% of D2, more preferably 10% to 30%, and even more preferably 15% to 25%. D1 and D2 are apparent diameters (Ferret diameters) measured by observation with a scanning electron microscope. The particle diameters are measured for 100 or more samples, and the arithmetic average values are taken as D1 and D2.
[0014] As described above, the support used in the present invention preferably contains titanium oxide. Among titanium oxides, it is more preferable to use one having electrical conductivity from the viewpoint of enhancing the activity of the electrode catalyst layer. From this viewpoint, the titanium oxide is preferably represented by the composition formula TiO X (wherein x is preferably in the range of 0.5≦x<2, and more preferably in the range of 0.5≦x<1.9). As the titanium oxide, for example, titanium dioxide (TiO 2) is known as a typical example, and it can be said that the titanium oxide represented by the above composition formula is in a state of oxygen deficiency compared to titanium dioxide. The present inventors believe that due to this oxygen deficiency state, the titanium oxide represented by the above composition formula has electrical conductivity.
[0015] Titanium oxide is Ti 4 O 7 , Ti 2 O 3 , TiO 0.5 , TiO or Ti 3 O 5 Among them, it is preferable that the crystalline phase of TiO 0.5 , TiO and Ti 4 O 7 is a particularly conductive material. Therefore, the support is crystalline TiO 0.5 , TiO or Ti 4 O 7 By including the carrier, the electrical conductivity of the carrier is increased, and the catalyst supported on the carrier can fully exhibit its performance.
[0016] Titanium oxide is Ti 4 O 7 , Ti 2 O 3 , TiO 0.5 , TiO or Ti 3 O 5 The fact that the titanium oxide has a crystalline phase can be confirmed by X-ray diffraction measurement (XRD) of the titanium oxide. 4 O 7 , Ti 2 O 3 , TiO 0.5 , TiO or Ti 3 O 5 The presence of only one crystal phase may be confirmed, or the presence of two or more crystal phases may be confirmed. When the titanium oxide has two or more crystal phases, the crystal phase may be composed of a main phase and a subphase. The main phase is a crystal phase that preferably occupies 30 mass% or more, more preferably 50 mass% or more. The subphase is a crystal phase that exists in a lower proportion than the main phase and is contained outside the main phase. The main phase is TiO 0.5 Or Ti 4 O 7 On the other hand, the subphase is preferably TiO or Ti 3 O 5 It is preferable that: Furthermore, titanium oxide is 4 O 7 , Ti 2 O 3 , TiO 0.5 , TiO or Ti 3 O 5 Other crystalline and amorphous phases of titanium oxides may be present. Examples of such oxides include TiO 2 Examples include TiO 2 When it exists as a crystalline phase, TiO 2 The TiO may be of the rutile type, anatase type, or brookite type. 2 It can also be confirmed by the above-mentioned XRD that the crystalline phase is present.
[0017] In titanium oxide, a portion of the titanium may be replaced by other elements (e.g., metal elements such as Nb, Ta, Mo, W, Ge, Sb, Bi, Hf, Zr, Mg, Ca, Sr, Ba, Zn, and Al).
[0018] The above-mentioned titanium oxide is suitably produced by, for example, the methods described in WO2013 / 141063 and WO2019 / 3788.
[0019] The catalyst-supporting carrier using the above-mentioned titanium oxide as a carrier preferably has a large BET specific surface area in terms of enhancing catalytic activity. 2 / g or more 30m 2 / g or less, and 2 / g or more 25m 2 / g or less is more preferable, 2 / g or more 25m 2 / g or less is more preferable. To realize a BET specific surface area in such a range, the catalyst support may be manufactured, for example, according to the method described below. The BET specific surface area can be measured by the nitrogen adsorption method according to the BET one-point method, using, for example, a "BELSORP-MR6" manufactured by Microtrack-Bell. The amount of powder to be measured is 0.3 g, and the preliminary degassing conditions are atmospheric pressure, 80°C, and 10 minutes.
[0020] The particle size of the catalyst-supporting carrier of the present invention is measured by a laser diffraction / scattering particle size distribution measurement method (for example, using a laser diffraction / scattering particle size distribution measurement device "LA-920" manufactured by Horiba, Ltd.) as a volume cumulative particle size D at a cumulative volume of 50% by volume. 50 In terms of particle size, it is preferably 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 50 μm or less, and even more preferably 0.1 μm or more and 20 μm or less. By setting the particle size of the catalyst-supporting carrier of the present invention within this range, the catalytic activity can be sufficiently increased.
[0021] In the catalyst-supported carrier, the amount of catalyst supported varies depending on the type of catalyst, but is generally preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 45% by mass or less, and even more preferably 15% by mass or more and 40% by mass or less, relative to the catalyst-supported carrier. By having the amount of catalyst supported within this range, sufficient catalytic activity can be expressed with the minimum amount required. The amount of catalyst supported can be measured by preparing a solution in which the catalyst-supported carrier is dissolved in, for example, an acid, and subjecting the solution to ICP emission spectrometry.
[0022] The amount of catalyst is preferably set appropriately in relation to the amounts of niobium, tantalum, zirconium, and silicon present on the surface of the electrode catalyst layer and in the vicinity thereof, from the viewpoint of exerting sufficient catalytic activity. From this viewpoint, the value of A2 / A3, which is the ratio of the atomic ratio A2 of the total of niobium, tantalum, zirconium, and silicon to the atomic ratio A3 of the catalyst on the surface of the electrode catalyst layer measured by XPS, is preferably set to 0.25 or more and 1.0 or less, and more preferably set to 0.30 or more and 0.60 or less. The value of A2 / A3 can be controlled by appropriately setting the conditions for disposing the coated oxide on the catalyst-supporting carrier and the conditions for supporting the catalyst on the carrier. The A2 / A3 value preferably satisfies the above-mentioned value when the electrode catalyst layer is in the state of being alone, or preferably satisfies the above-mentioned value when in the state of being a CCM or MEA, or more preferably satisfies the above-mentioned value when the electrode catalyst layer is incorporated into a fuel cell, before and / or after the operation of the fuel cell.
[0023] The catalyst used in the present invention preferably contains platinum, because platinum has high hydrogen oxidation activity. From this viewpoint, the catalyst preferably contains platinum or an alloy of platinum and at least one of iridium and ruthenium. The catalyst may be partially oxidized in the environment in which it is used.
[0024] The electrode catalyst layer may contain other components in addition to the catalyst-supporting carrier. The electrode catalyst layer may contain, for example, an ionomer. The ionomer preferably has proton conductivity. When the electrode catalyst layer of the present invention contains an ionomer, the performance of the catalyst layer is further improved. As the ionomer, for example, a polymer material having a structure in which a perfluoroether pendant side chain having a sulfonic acid group at its terminal is bonded to a polytetrafluoroethylene main chain can be used. As such an ionomer, for example, Nafion (registered trademark), Flemion (registered trademark), Aciplex (registered trademark), Fumion F (registered trademark), etc. can be mentioned.
[0025] When the electrode catalyst layer contains an ionomer, it is advantageous to adjust the amount of the ionomer and the amount of the catalyst-supporting carrier in terms of improving the performance of the electrode catalyst layer. For example, in the electrode catalyst layer, from the viewpoint of being able to sufficiently cover the catalyst or the catalyst-supporting carrier with the ionomer and to easily respond to changes in relative humidity in the external environment, the value of I / M, which is the ratio of the mass I of the ionomer to the mass M of the catalyst-supporting carrier, is preferably 0.06 or more, more preferably 0.07 or more. On the other hand, from the viewpoint of being able to suppress the increase in electrical resistance due to the high proportion of the ionomer present and to suppress the elution of titanium, the value of I / M is preferably 0.25 or less, more preferably 0.22 or less, and even more preferably 0.20 or less. Note that the ionomer is often provided in the form of a dispersion, and the mass I of the ionomer refers to the mass of the solid content in the dispersion.
[0026] Next, a method for producing the electrode catalyst layer will be described. First, a method for producing the carrier used in the electrode catalyst layer will be described. In producing the carrier, metallic titanium and TiO are used as starting materials. 2 For metallic titanium, D 50 The use of titanium metal powder having a particle size of 0.5 μm or more and 300 μm or less is preferable for the purpose of improving the adhesion between titanium metal and TiO 2 From the same viewpoint, TiO 2 As D 50 It is preferable to use a powder having a particle size of 0.01 μm or more and 5.0 μm or less. 2 Any of the rutile type, anatase type, and brookite type TiO can be used. From the viewpoint of obtaining a support with a high specific surface area, anatase type TiO 2 It is preferable to use:
[0027] In the manufacture of the support, titanium metal and TiO 2 The mixing ratio is as follows: X Generally speaking, TiO is added to 100 parts by mass of metallic titanium. 2are mixed in an amount of preferably 20 parts by mass or more and 300 parts by mass or less, more preferably 40 parts by mass or more and 230 parts by mass or less, and even more preferably 50 parts by mass or more and 180 parts by mass or less. For mixing, a device capable of general dry mixing, such as a mortar, an automatic mortar, a ball mill, a stamp mill, a V-type mixer, or a tumbler-type mixer, can be used.
[0028] Titanium metal and TiO 2 After mixing, the mixture is fired to produce titanium oxide. The firing is generally carried out in a vacuum. The degree of vacuum in this case is 1×10 absolute pressure. -1 From the viewpoint of successfully obtaining the target titanium oxide, it is preferable that the calcination temperature is 600° C. or more and 1300° C. or less, and more preferably 750° C. or more and 1100° C. or less. Provided that the calcination temperature is within the above-mentioned range, the calcination time is preferably 5 hours or more and 30 hours or less, and more preferably 5 hours or more and 15 hours or less.
[0029] The above steps provide a titanium oxide carrier. Next, the catalyst is supported on the carrier to obtain a catalyst-supported carrier. It is preferable to adjust the particle size of the carrier prior to supporting the catalyst. For adjusting the particle size, a grinding device such as a paint shaker or a bead mill can be used. In this case, it is preferable to grind the carrier in an organic solvent in order to prevent the carrier from coming into contact with oxygen and being oxidized. Examples of organic solvents used for this purpose include aliphatic monohydric alcohols such as ethanol, 2-propanol, and butanol, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as hexane, and other ketones, esters, and ethers. From the viewpoint of successful grinding, the ratio of the carrier and the organic solvent used is preferably 100 parts by mass or more and 9900 parts by mass or less, and more preferably 100 parts by mass or more and 900 parts by mass or less, per 100 parts by mass of the carrier.
[0030] After the crushing of the carrier in the organic solvent is completed, the catalyst loading step is carried out. In this case, it is preferable to prevent the catalyst from coming into contact with oxygen as much as possible even during the period from crushing to catalyst loading from the viewpoint of preventing oxidation of the carrier. For this purpose, it is advantageous to load the catalyst on the carrier dispersed in the organic solvent without carrying out the drying step on the crushed carrier. In other words, it is advantageous to crush the carrier in the organic solvent and then load the catalyst in the organic solvent without carrying out the drying step. The organic solvent used for crushing and the organic solvent used for loading the catalyst may be the same or different.
[0031] For the support of the catalyst, a raw material containing an element constituting the catalyst, for example, platinum, can be used. By mixing such a raw material with a carrier dispersed in an organic solvent, the element constituting the catalyst is attached to the surface of the carrier. In this case, the dispersion may be heated as necessary. For example, when the catalyst contains platinum, raw materials containing an element constituting the catalyst may include hexachloroplatinate, dinitrodiammine platinum salt, hexaammine platinum chloride, tetraammine platinum hydroxide, acetylacetonato platinum salt, etc. When the catalyst contains iridium, iridium oxide, iridium chloride, acetylacetonato iridium salt, etc. can be used. When the catalyst contains ruthenium, ruthenium chloride, ruthenium oxide, ruthenium nitrate, hexaammine ruthenium chloride, acetylacetonato ruthenium salt, etc. can be used.
[0032] In this way, after the elements constituting the catalyst are supported on the carrier, the carrier is subjected to a calcination process to generate a catalyst on the surface of the carrier. The calcination can generally be carried out under a reducing atmosphere. As the reducing atmosphere, a mixed gas of hydrogen gas and an inert gas such as argon gas or nitrogen gas is preferably used. In this case, the degree of reduction can be controlled by adjusting the ratio of hydrogen gas and the inert gas in the mixed gas. From the viewpoint of appropriately controlling the degree of reduction, the calcination temperature is preferably 400°C or more and 1200°C or less, and more preferably 550°C or more and 900°C or less. The calcination time is preferably 0.1 hours or more and 20 hours or less, and more preferably 1 hour or more and 10 hours or less, provided that the calcination temperature is within the above-mentioned range.
[0033] In this way, a catalyst-supported carrier is obtained in which a catalyst is supported on the surface of a carrier containing titanium oxide. Next, a coating oxide is arranged on the surface of the catalyst-supported carrier. For example, a liquid phase deposition method (LPD method), an evaporation to dryness method, an atomic layer deposition method (ALD method), etc. are used to arrange the coating oxide. These methods will be described below.
[0034] [LPD method] The LPD method is a method for directly synthesizing an oxide thin film on a base material from an aqueous solution by utilizing the hydrolysis equilibrium reaction of a metal fluoro complex in an aqueous solution. The reaction in the LPD method can be summarized by the following chemical reaction formula.
[0035] <Precipitation equilibrium reaction> MF x (x-2n)- +nH 2 O=MO n +xF - +2nH + (1) (In the formula, M represents an oxide element.) <Precipitation-driven reaction> H 3 BO 3 +4H + +4F - =HBF 4 +3H 2 O (2) Al3+ +6H + +6F - =H 3 AlF 6 +3H + (3)
[0036] In the LPD method, the metal fluoro complex MF in an aqueous solution represented by the above formula (1) is x (x-2n)- The main reaction is the hydrolysis equilibrium reaction (ligand exchange reaction) of the above. To this reaction system, an agent for forming a fluorine compound more stable than the metal fluoro complex (hereinafter also referred to as a fluoride ion trapping agent) and the catalyst-supported carrier are added. For example, by adding boric acid or aluminum ions, which are fluoride ion trapping agents, to the reaction system, a more stable complex is formed according to the reaction of formula (2) or (3). The formation of this complex consumes free fluoride ions, shifting the equilibrium of formula (1) toward the deposition of metal oxide. This causes the reaction of formula (1) to proceed spontaneously, and the oxide that becomes supersaturated in the aqueous solution gradually deposits on the surface of the catalyst-supported carrier added to the aqueous solution.
[0037] When the coating oxide contains niobium oxide, niobium pentoxide (Nb 2 O 5 ) was used, and the aqueous solution of this metal fluoro complex was added with boric acid (H 3 BO 3 ) is added, and then the catalyst-supporting carrier is further added thereto. When the coating oxide contains an oxide of tantalum, tantalum pentoxide (Ta 2 O 5 ) was used, and the aqueous solution of this metal fluoro complex was added with boric acid (H 3 BO 3 ) is added, and then the catalyst-supporting carrier is further added thereto.
[0038] When the coating oxide contains zirconium oxide, fluorozirconate (H 2 ZrF 6) was used, and aluminum ions (Al 3+ ) is added, and then the catalyst-supporting carrier is further added thereto.
[0039] When an oxide is formed on the surface of the catalyst-supporting carrier, a heat treatment is performed to stabilize the oxide. The heat treatment can generally be performed in an oxygen-containing atmosphere such as an air atmosphere, or can be performed in a reducing atmosphere. An example of the reducing atmosphere is an inert gas atmosphere (e.g., an argon atmosphere) containing preferably 1 vol% to 4 vol% hydrogen. By performing the heat treatment in a reducing atmosphere, the valence of the coating oxide can be kept low. The heat treatment temperature is preferably 400°C to 900°C, more preferably 500°C to 700°C, from the viewpoint of stabilizing the oxide. From the same viewpoint, the heat treatment time is preferably 1 hour to 10 hours.
[0040] [Evaporation to dryness method] In the evaporation to dryness method, a coupling agent containing an element constituting the coating oxide is used. When the element constituting the coating oxide is, for example, silicon, a silane coupling agent may be used.
[0041] The catalyst-supported carrier is dispersed in an organic solvent, for example, a monohydric alcohol such as ethanol, and a coupling agent is added under this condition, and the dispersion is mixed. Next, a catalyst for the coupling agent is added to the dispersion to initiate the coupling reaction. The coupling reaction causes hydrolysis of the coupling agent and subsequent dehydration condensation, producing a condensation polymer of the coupling agent on the surface of the catalyst-supported carrier. The dispersion may be heated to facilitate the coupling reaction.
[0042] After the coupling reaction is completed, the dispersion is evaporated to dryness to obtain a solid content. The solid content is then subjected to a heat treatment to oxidize the condensation polymer and generate the desired coated oxide. The heat treatment can generally be performed in an oxygen-containing atmosphere such as air, or can be performed in a reducing atmosphere. Specific examples of the reducing atmosphere are as described above. The heat treatment temperature is preferably 400°C or higher and 900°C or lower from the viewpoint of reliable generation of the oxide. From the same viewpoint, the heat treatment time is preferably 1 hour or higher and 10 hours or lower.
[0043] [ALD method] In the ALD method, a precursor gas containing an element constituting the coating oxide is introduced into a chamber in which a catalyst-supported carrier is placed. Then, molecules of the precursor gas are adsorbed on the surface of the catalyst-supported carrier. When the element constituting the coating oxide is, for example, zirconium, for example, bis(methyl-η5-cyclopentadienyl)methoxymethylzirconium and tetrakis(ethylmethylamino)zirconium can be used as the precursor gas.
[0044] Next, the precursor gas remaining in the chamber is removed, and then humidified argon plasma-excited gas is introduced into the chamber. The precursor gas is oxidized by the action of this gas, and one oxide layer is formed on the surface of the catalyst-supporting carrier. This operation is repeated until an oxide layer of the desired thickness is obtained.
[0045] Once an oxide layer of a desired thickness has been formed on the surface of the catalyst-supporting carrier in this manner, a heat treatment is carried out to stabilize the oxide. The heat treatment can generally be carried out in an oxygen-containing atmosphere such as air, or in a reducing atmosphere. Specific examples of the reducing atmosphere are as described above. From the viewpoint of stabilizing the oxide, the heat treatment temperature is preferably 150°C or higher and 700°C or lower. From the same viewpoint, the heat treatment time is preferably 1 hour or higher and 10 hours or lower.
[0046] After the catalyst-supporting carrier having the coating oxide disposed on the surface thereof is obtained by each of the above methods, a dispersion liquid containing the catalyst-supporting carrier is prepared. To prepare the dispersion liquid, the catalyst-supporting carrier is mixed with a solvent. An ionomer is also added during mixing, if necessary.
[0047] As the solvent used for dispersion, it is preferable to use a primary alcohol. Examples of the primary alcohol include those having 1 to 10 carbon atoms. Among these, it is preferable to use a saturated aliphatic alcohol. Examples include methanol, ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, and decanol. In particular, it is preferable to use a saturated aliphatic alcohol having 1 to 4 carbon atoms. The primary alcohol can be used alone or in combination of two or more. In addition, other solvents than the above-mentioned primary alcohols, such as aliphatic monohydric alcohols such as 2-propanol, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as hexane, and other organic solvents such as ketones, esters, and ethers, or water, can also be used.
[0048] The dispersion medium used for dispersion is preferably spherical, with the diameter of the sphere being preferably 0.1 mm to 8 mm, more preferably 0.5 mm to 5 mm, and even more preferably 1 mm to 3 mm.
[0049] In this way, when a dispersion of a catalyst-supported carrier having a coated oxide disposed on its surface is obtained, an electrode catalyst layer is formed from the dispersion. The electrode catalyst layer is formed, for example, by applying the dispersion to an object to be coated using various coating devices to form a coating film, and then drying the coating film. The object to be coated may be, for example, a film of a fluorine-based resin such as polytetrafluoroethylene. The electrode catalyst layer formed on the object to be coated is superimposed on, for example, a solid electrolyte membrane and heat-pressed to transfer the electrode catalyst layer to the surface of the solid electrolyte membrane. This transfer results in a CCM in which an electrode catalyst layer is disposed on one surface of the solid electrolyte membrane.
[0050] The electrode catalyst layer thus formed is preferably used as an electrode catalyst layer of a polymer electrolyte fuel cell. It is particularly preferable to use the electrode catalyst layer as an anode catalyst layer, taking advantage of the characteristic that the carrier has high resistance under a hydrogen atmosphere. The anode preferably includes an electrode catalyst layer and a gas diffusion layer. The gas diffusion layer functions as a supporting current collector having a current collecting function. Furthermore, the gas diffusion layer has a function of sufficiently supplying gas to the electrode catalyst layer. For example, carbon paper or carbon cloth, which is a porous material, can be used as the gas diffusion layer. Specifically, for example, the gas diffusion layer can be formed by carbon cloth woven with yarns in a predetermined ratio of carbon fibers whose surfaces are coated with polytetrafluoroethylene and carbon fibers that are not coated.
[0051] Examples of solid electrolyte membranes include perfluorosulfonic acid polymer-based proton conductor membranes, membranes in which inorganic acids such as phosphoric acid are doped into hydrocarbon polymer compounds, organic / inorganic hybrid polymers in which a portion of the polymer is substituted with functional groups of a proton conductor, and proton conductors in which a polymer matrix is impregnated with a phosphoric acid solution or a sulfuric acid solution.
[0052] A membrane electrode assembly consisting of an electrode catalyst layer, a solid electrolyte membrane, and a gas diffusion layer is provided with separators on each surface thereof to form a polymer electrolyte fuel cell. As the separator, for example, a separator having a plurality of protrusions (ribs) extending in one direction formed at a predetermined interval on the surface facing the gas diffusion layer can be used. A groove having a rectangular cross section is formed between adjacent protrusions. This groove is used as a flow path for supplying and discharging a fuel gas and an oxidant gas such as air. The fuel gas and the oxidant gas are supplied from a fuel gas supply means and an oxidant gas supply means, respectively. The separators arranged on each surface of the membrane electrode assembly are preferably arranged so that the grooves formed therein are perpendicular to each other. The above configuration constitutes the minimum unit of a fuel cell, and a fuel cell can be constructed from a cell stack consisting of tens to hundreds of such configurations arranged in parallel. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0054] Example 1 (1) Carrier manufacturing process 6.7 g of metallic titanium and 3.7 g of anatase TiO 2 The mixture was mixed and sintered in a vacuum furnace at 900°C for 10 hours. The absolute pressure in the vacuum furnace was 10 -1 The pressure was set to 0.05 Pa or less. A support made of titanium oxide was obtained by this calcination. Crystal structure analysis by powder X-ray diffraction (XRD) revealed that this titanium oxide had the composition formula TiO 0.5 It was confirmed that the above formula is expressed as follows.
[0055] (2) Catalyst loading process A slurry was obtained by mixing 4.0 g of the carrier obtained in (1) above with 16.0 g of ethanol. The carrier in the slurry was pulverized for 10 hours using a paint shaker. Next, 300 g of ethanol and 8 mL of dinitroammine platinum nitrate aqueous solution (platinum concentration 15%) were added to the slurry to obtain a mixed liquid. This mixed liquid was placed in a four-neck flask. The mixed liquid in the flask was heated in an oil bath for 6 hours so that the liquid temperature reached 75°C. The liquid was then cooled and further washed with water to remove ethanol and auxiliary salt components. The cake thus obtained was vacuum dried to obtain a dry powder.
[0056] (3) Firing process The dried powder obtained in (2) above was sintered. The sintering atmosphere was 2 vol% H 2The mixture gas was 0.1 μm / Ar (remainder). The firing temperature was 600° C., and the firing time was 2 hours. In this way, a catalyst-supported carrier was obtained on which platinum was supported as a catalyst. The particle size D2 of the catalyst-supported carrier measured by the above-mentioned method using a scanning electron microscope was 0.12 μm. In addition, the volume cumulative particle size D2 at 50% cumulative volume of the catalyst-supported carrier measured by a laser diffraction scattering type particle size distribution measurement method was 0.12 μm. 50 The particle size D was 0.21 μm. 50 was measured by mixing the catalyst-supporting carrier particles with ethanol, dispersing the mixture in a general ultrasonic bath for 1 minute, and then measuring the dispersion properties by the above-mentioned method. X-ray diffraction measurements of the catalyst support revealed that the main phase of this titanium oxide has the formula TiO 0.5 It was confirmed that the subphase was represented by TiO. 2 was also observed.
[0057] (4) Formation of the coating oxide by LPD method Nb 2 O 5 was dissolved in an aqueous solution of ammonium hydrogen fluoride to obtain an aqueous solution with a niobium concentration of 50 mmol / L. 50 mL of this aqueous solution and 100 g of water were added to 5 g of a catalyst-supported carrier to obtain a slurry. 100 mL of an aqueous solution of 0.5 mol / L boric acid was added to this slurry, and the mixture was stirred at 50°C for 2 hours. This resulted in the formation of niobium oxide on the surface of the catalyst-supported carrier. Next, the slurry was subjected to solid-liquid separation, and the solid content was washed and dried, and then subjected to heat treatment at 600°C for 1 hour in an air atmosphere. This resulted in the formation of a coating oxide containing niobium on the surface of the catalyst-supported carrier.
[0058] (5) Dispersion process The catalyst-supported carrier obtained in (4) and yttrium-stabilized zirconia balls (Vickers hardness 12 GPa) with a diameter of 1 mm were placed in a container, and pure water, ethanol, and 2-propanol were added in this order as solvents in a mass ratio of 15:50:35. The mixture thus obtained was dispersed by ultrasonic waves for 3 minutes. Then, the mixture was stirred at 800 rpm for 20 minutes with a planetary ball mill (ARE310 manufactured by Thinky Corporation). Furthermore, 5% Nafion (registered trademark) (274704-100ML, manufactured by Sigma-Aldrich) was added as an ionomer to the mixture, and the same stirring as above was performed by ultrasonic dispersion and planetary ball mill. The value of I / M, which is the ratio of the mass I of the ionomer to the mass M of the catalyst-supported carrier, was set to 0.11. In this way, a dispersion was obtained.
[0059] (6) Electrode catalyst layer formation process The dispersion obtained in (5) was applied onto a polytetrafluoroethylene sheet using a bar coater, and the coating was dried at 60° C. to obtain an electrode catalyst layer. The value of I / M, which is the ratio of the mass I of the ionomer to the mass M of the catalyst-supporting carrier in the electrode catalyst layer, was as shown in Table 1 below.
[0060] [Examples 2 to 4] A coating oxide containing niobium was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 1, except that the amount of the niobium aqueous solution in step (4) of Example 1 was changed, and the catalyst-supporting carrier was used to form an electrode catalyst layer. When the crystal structure of the carrier was analyzed by powder X-ray diffraction (XRD), it was found that the main phase of this titanium oxide was represented by the formula TiO 0.5 It was confirmed that the subphase was represented by TiO.
[0061] Example 5 In step (4) of Example 1, Nb 2 O 5 Instead of Ta 2 O 5 Using Ta 2 O 5was dissolved in an aqueous solution of ammonium hydrogen fluoride to obtain an aqueous solution with a tantalum concentration of 50 mmol / L. A coated oxide containing tantalum was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 1, except for using this aqueous tantalum solution, and an electrode catalyst layer was formed using the catalyst-supporting carrier.
[0062] Example 6 The carrier manufacturing process, catalyst supporting process, and calcination process were the same as in Example 1. When the carrier was subjected to crystal structure analysis by powder X-ray diffraction (XRD), it was found that the main phase of this titanium oxide was represented by the composition formula TiO 0.5 It was confirmed that the subphase was represented by TiO. The evaporation to dryness method was used for the coating oxide formation process. The evaporation to dryness method was carried out as follows. 60g of ethanol was added to 0.5g of catalyst-supported carrier to obtain a slurry. 0.1g of a silane coupling agent (KBE-1003: manufactured by Shin-Etsu Chemical Co., Ltd.) was added to this slurry, and the slurry was heated to 150°C. Under this condition, a 10% aqueous hydrochloric acid solution was added to the slurry to initiate the coupling reaction of the silane coupling agent. The amount added was 0.75mL. After the coupling reaction was completed, the slurry was heated at 150°C to evaporate the slurry to dryness. The solid content remaining after evaporation to dryness was subjected to heat treatment at 600°C for 1 hour in an air atmosphere. This resulted in the formation of a silicon-containing coated oxide on the surface of the catalyst-supported carrier, and the catalyst-supported carrier was used to form an electrode catalyst layer. The dispersion step and the electrode catalyst layer formation step were the same as in Example 1.
[0063] Example 7 A silicon-containing coated oxide was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 6, except that the amount of the silane coupling agent used in Example 6 was changed, and the catalyst-supporting carrier was used to form an electrode catalyst layer.
[0064] Example 8 Metallic titanium and anatase type TiO used in step (1) of Example 1 2 By changing the mixing ratio of Ti 4 O 7The titanium oxide was produced by powder X-ray diffraction (XRD) analysis of the crystal structure. The main phase of the titanium oxide was found to be composed of the formula Ti 4 O 7 , the subphase is Ti 3 O 5 It was confirmed that the titanium oxide was expressed by the formula: ##EQU1## In the same manner as in Example 1, except that this titanium oxide was used as the carrier, a coating oxide containing niobium was formed on the surface of the catalyst-supported carrier, and the catalyst-supported carrier was used to form an electrode catalyst layer. The particle diameter D2 of the catalyst-supported carrier measured by the above-mentioned method was 0.16 μm. The volume cumulative particle diameter D 50 was 0.25 μm.
[0065] Example 9 In step (4) of Example 1, Nb 2 O 5 Instead of ZrO 2 Using ZrO 2 was dissolved in an aqueous solution of ammonium hydrogen fluoride to obtain an aqueous solution with a zirconium concentration of 50 mmol / L. A coating oxide containing zirconium was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 1, except for using this aqueous zirconium solution, and an electrode catalyst layer was formed using the catalyst-supporting carrier. A crystal structure analysis was performed by powder X-ray diffraction (XRD), and it was found that the main phase of the titanium oxide was represented by the composition formula TiO 0.5、 The subphase was identified as TiO.
[0066] [Examples 10 to 12] A coating oxide containing niobium was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 1, except that the amount of the niobium aqueous solution in step (4) of Example 1 was changed, and the catalyst-supporting carrier was used to form an electrode catalyst layer. When the crystal structure of the carrier was analyzed by powder X-ray diffraction (XRD), it was found that the main phase of the titanium oxide was represented by the formula TiO 0.5 It was confirmed that the subphase was represented by TiO.
[0067] Example 13 A coated oxide containing niobium was formed on the surface of a catalyst-supporting carrier in the same manner as in Example 1, except that an iridium nitrate solution (iridium concentration 8.7%) was added together with a dinitroammine platinum nitrate aqueous solution (platinum concentration 15%), which was the catalyst metal raw material, in step (2) of Example 1. The amount of each aqueous solution added was 6 mL.
[0068] Comparative Example 1 In this comparative example, the stirring time of the boric acid aqueous solution in step (4) of Example 1 was shorter than that of the same Example, and the amount of the coating oxide containing niobium was smaller than that of the same Example. Specifically, the stirring time of the boric acid aqueous solution was set to 30 minutes. Other than this, the same procedure as in Example 1 was followed to generate a coating oxide containing niobium on the surface of a catalyst-supporting carrier, and the catalyst-supporting carrier was used to form an electrode catalyst layer.
[0069] Comparative Example 2 In this comparative example, the stirring time of the boric acid aqueous solution in step (4) of Example 1 was longer than that of the same Example, and the amount of the coated oxide containing niobium was larger than that of the same Example. Specifically, the stirring time of the boric acid aqueous solution was 24 hours. Other than this, in the same manner as in Example 1, the coated oxide containing niobium was generated on the surface of the catalyst-supported carrier, and the catalyst-supported carrier was used to form an electrode catalyst layer.
[0070] Comparative Example 3 This comparative example corresponds to an example of Patent Document 1 (JP 2016-081584 A). (1) Carrier manufacturing process The same as in Example 1 of this specification. (2) Formation of the coating oxide by LPD method Nb 2 O 5It was dissolved in an aqueous solution of ammonium hydrogen fluoride to obtain an aqueous solution with a niobium concentration of 50 mmol / L. 50 mL of this aqueous solution and 100 g of water were added to 5 g of a carrier to obtain a slurry. 100 mL of a 0.5 mol / L boric acid aqueous solution was added to this slurry, and stirring was carried out at 50 °C for 2 hours. Thereby, niobium oxide was formed on the surface of the carrier. Next, the slurry was subjected to solid-liquid separation, the solid content was washed and dried, and then heat-treated at 600 °C for 1 hour in an air atmosphere. Thereby, a coated oxide containing niobium was formed on the surface of the carrier. (3) Catalyst loading step 4.0 g of the carrier obtained in (2) above and 16.0 g of ethanol were mixed to obtain a slurry. The carrier in the slurry was pulverized by a paint shaker for 10 hours. Next, 300 g of ethanol and 8 mL of a dinitroammineplatinum nitrate aqueous solution (platinum concentration 15%) were added to the slurry to obtain a mixed solution. This mixed solution was put into a four-necked flask. The mixed solution in the flask was heated in an oil bath at 75 °C for 6 hours so that the liquid temperature became 75 °C. Then, the liquid was cooled and further washed with water to remove ethanol and by-product salt components. The cake thus obtained was vacuum dried to obtain dry powder. (4) Firing step The dry powder obtained in (3) above was fired. The firing atmosphere was a mixed gas of 2 vol% H 2 / the remaining Ar. The firing temperature was 600 °C. The firing time was 2 hours. In this way, a catalyst-supported carrier with platinum supported thereon as a catalyst was obtained. Thereafter, an electrode catalyst layer was formed in the same manner as in Example 1.
[0071] 〔Evaluation 1〕 For the electrode catalyst layers obtained in the examples and comparative examples, measurements were carried out by XPS according to the following procedure to obtain the values of A2 / A1 and A2 / A3. Also, the particle size D1 and BET specific surface area of the coated oxide were measured by the above method. The results are shown in Table 1 below. In Table 1, since the coated oxides of Examples 6 and 7 and Comparative Example 3 were in a film form, the measurement of the particle size D1 of the coated oxide was not carried out.
[0072] <Measurement procedure of XPS method> The surface of the electrode catalyst layer was analyzed using an XPS measuring device, PHI Quantes, manufactured by ULVAC-PHI, Inc. The measurement conditions were as follows: Excitation X-ray: Monomer Al-Kα line (1486.7 eV) Output: 100W Acceleration voltage: 100kV ·X-ray irradiation diameter: 100μmφ ·Measurement area: 300μm×600μm Pass energy: 26.0eV Energy step: 0.1eV / step
[0073] [Evaluation 2] A polymer electrolyte fuel cell was produced using the electrode catalyst layer obtained in the examples and comparative examples, and the cell voltage was measured. The electrode catalyst layer obtained in the examples and comparative examples was used as an anode catalyst layer. The cathode catalyst layer was obtained by the following method. 1.00 g of platinum-supported carbon black (TEC10E50E) manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. and a 10 mm diameter yttrium-stabilized zirconia ball were placed in a container, and pure water, ethanol, and 2-propanol were added in order in a mass ratio of 45:35:20 (10.2 g as a mixed solution). The mixed solution thus obtained was dispersed by ultrasonic waves for 3 minutes. Next, the mixture was stirred at 800 rpm for 20 minutes using a planetary ball mill (ARE310 manufactured by Thinky Corporation). Furthermore, 5% Nafion (registered trademark) (274704-100ML, manufactured by Sigma-Aldrich) was added as an ionomer to the mixed solution, and the same stirring as above was continued by ultrasonic dispersion and a planetary ball mill. The amount of Nafion added was such that the mass ratio of Nafion to platinum-supported carbon black was 70.0. The dispersion thus obtained was applied onto a polytetrafluoroethylene sheet using a bar coater, and the coating was dried at 60°C.
[0074] The anode and cathode catalyst layers formed on the polytetrafluoroethylene sheets were cut into squares measuring 54 mm on each side, and then laminated with an electrolyte membrane made of Nafion (registered trademark) (NRE-212, manufactured by DuPont). The resulting electrolyte membrane was then heated at 140°C and 25 kgf / cm 2 The transfer was performed by heat pressing in the atmosphere for 2 minutes under the condition of 100° C. In this manner, the cathode and anode catalyst layers were formed on each side of the solid electrolyte membrane made of Nafion, to obtain a CCM.
[0075] The obtained CCM was sandwiched between a pair of gas diffusion layers (manufactured by SGL Carbon Co., Ltd., model number: 29BC). It was further sandwiched between a pair of separators made of carbon plates with gas flow paths formed therein to produce a polymer electrolyte fuel cell. The fuel cell thus obtained corresponds to the JARI standard cell.
[0076] Hydrogen gas was supplied to the anode side of the polymer electrolyte fuel cell, and oxygen gas was supplied to the cathode side. The flow rates were set so that the hydrogen gas utilization rate was 70% and the oxygen utilization rate was 40%. The gases were each humidified using an external humidifier before being supplied to the fuel cell. The temperature of the fuel cell was adjusted to 80°C, and the humidity of the supplied gas was adjusted so that the relative humidity was 100% RH. The relationship between the cell voltage and current density at this time was measured. From the obtained relationship between the cell voltage and current density, it was found that the current density of 0.1 A / cm 2 and 1A / cm 2 The cell voltage value V at 0.1 A / cm was obtained. The results are shown in Table 1 below. 2 The current density of 1 A / cm is suitable for evaluating catalytic activity. 2 This current density is suitable for evaluating the cell resistance.
[0077] [Rating 3] For the polymer electrolyte fuel cells prepared by the method described in [Evaluation 2], the current density retention rate after long-term operation was measured by the following procedure. The results are shown in Table 1 below. (1) First Step Hydrogen gas was supplied to the anode side of the polymer electrolyte fuel cell, and air was supplied to the cathode side. The flow rates were set so that the hydrogen gas utilization rate was 70% and the oxygen utilization rate was 40%. The gases were humidified using an external humidifier before being supplied to the fuel cell. The temperature of the fuel cell was adjusted to 80°C, and the humidity of the supplied gas was adjusted so that the relative humidity was 100% RH. The relationship between the cell voltage and current density at this time was measured, and the current density I 1 The value of was calculated. (2) Second Step Next, hydrogen gas was supplied to the anode side of the polymer electrolyte fuel cell, and oxygen was supplied to the cathode side. The flow rates were set so that the hydrogen gas utilization rate was 70% and the oxygen utilization rate was 40%. The gases were each humidified using an external humidifier before being supplied to the fuel cell. The temperature of the fuel cell was adjusted to 110°C, and the humidity of the supplied gas was adjusted to a relative humidity of 53% RH. Under these conditions, a current density of 0.4 A / cm 2 I drove for 30 hours. (3) Third Step Using the same procedure as in step 1, the current density I 2 The value of was calculated. (4) Fourth Step (I 2 / I 1 ) × 100 was calculated, and this value was taken as the current density maintenance rate.
[0078] [Rating 4] For the solid polymer electrolyte fuel cells fabricated using the electrode catalyst layers obtained in Example 1 and Comparative Example 1, the fluorine concentration in the wastewater on the cathode side was measured. As a method for evaluating the deterioration of electrolyte membranes and ionomers, a method for evaluating the amount of fluorine discharged has been established in the technical field. Furthermore, General Motors reported at the 235th ECS Meeting that under the operating conditions of a fuel cell using a material containing titanium, the concentration of fluorine contained in wastewater increases, and that titanium is detected on the cathode side (electrode not using titanium) when the concentration of fluorine discharge increases. From these findings, the present inventor believes that there is a correlation between the amount of titanium eluted and the concentration of fluorine contained in the wastewater on the cathode side. Therefore, the present inventor believes that the degree of titanium elution can be evaluated by measuring the concentration of fluorine contained in the wastewater on the cathode side. Therefore, the concentration of fluorine contained in the wastewater on the cathode side was measured by the method described below. The wastewater from the cathode side of a fuel cell operating for a long period of time (30 hours) was stored, and the fluorine concentration in the wastewater was analyzed using an ion chromatograph analyzer (IC-2020, manufactured by Tosoh Corporation). The total amount of fluorine emitted during long-term operation was calculated from the analyzed fluorine concentration and the stored water during long-term operation, and the fluorine emission amount (mg / cm) was calculated by dividing the total amount of fluorine emitted by the electrode area. 2 / 30h).
[0079] [Table 1]
[0080] As is clear from the results shown in Table 1, the fuel cells produced using the electrode catalyst layers obtained in each Example have a higher cell voltage than the fuel cells of the Comparative Examples. It is also clear that the fuel cells produced using the electrode catalyst layers obtained in each Example have a higher current density retention rate than the fuel cells of the Comparative Examples. These mean that the electrode catalyst layers obtained in each Example have higher catalytic activity than the electrode catalyst layers obtained in the Comparative Examples, and that the decrease in catalytic activity is suppressed. Furthermore, as is clear from the results shown in the table, the fuel cell of Example 1 has a lower concentration of fluorine in the wastewater on the cathode side compared to the fuel cell of Comparative Example 1. This means that the elution of titanium is suppressed in the fuel cell of Example 1 compared to the fuel cell of Comparative Example 1. [Industrial Applicability]
[0081] As described above in detail, according to the present invention, in a fuel cell using titanium oxide as a catalyst support, it is possible to suppress the elution of titanium during operation, particularly the elution of titanium from the anode, while maintaining catalytic activity.
Claims
1. A fuel cell electrode catalyst layer including a catalyst-supported carrier in which a catalyst is supported on a carrier, the support comprises titanium oxide; The catalyst-supporting carrier has an oxide of at least one element selected from the group consisting of niobium, tantalum, zirconium, and silicon on its surface, An electrode catalyst layer for a fuel cell, in which the value A2 / A1, which is the ratio of the atomic ratio A2 of the sum of niobium, tantalum, zirconium and silicon to the atomic ratio A1 of titanium on the surface of the catalyst layer as measured by X-ray photoelectron spectroscopy, is 0.35 or more and 1.70 or less.
2. The titanium oxide is TiO X The electrode catalyst layer according to claim 1 , having a composition of (0.5≦x<2).
3. 3. The electrode catalyst layer according to claim 1, wherein the catalyst comprises platinum or an alloy of platinum with at least one of iridium and ruthenium.
4. Further comprising an ionomer, 4. The electrode catalyst layer according to claim 1, wherein a value I / M, which is a ratio of a mass I of the ionomer to a mass M of the catalyst-supporting carrier, is 0.06 or more and 0.25 or less.
5. 5. A polymer electrolyte fuel cell comprising the electrode catalyst layer according to claim 1 as an anode catalyst layer.
Citation Information
Patent Citations
Electrocatalyst for fuel cells, and method for manufacturing the electrocatalyst.
JP2015502646A
Conductive particle and carrier material comprising the same, and fuel cell device and water electrolytic device
JP2016081584A
Catalyst, method for producing catalyst, oxidizing method, oxidizing article, and oxidizing apparatus
WO2005068071A1